Frustrated self-assembly of non-Euclidean crystals of nanoparticles - Francesco Serafin (Nature Portfolio, 2021)
Widely existing self-organised complex structures in nature exhibit a high level of sophistication, yet can one program the self-assembly process to achieve similar result in the lab remains unanswered. Here, Serafin et al. present a non-Euclidean self-assembly theory for polyhedral nanoparticles that offers insight on how to manipulate the process for realising new material capabilities.